ASUHAN KESEHATAN GIGI MULUT PADA KLIEN TN.S KASUS KARANG GIGI DISERTAI KELAINAN GIGI SUPERNUMERARY (Politeknik Kesehatan Kemenkes Bandung, 2020)
ABSTRACT The conditions of the Supernumerary Teeth sometimes become a problem for the sufferer. Supernumerary teeth can cause the teeth to be crowded making it difficult to clean with brushing your teeth, this condition can cause a buildup of plaque that is also one the risk factors for the occurrence of tartar. The tartar is a hard sediment which is located on the surface of the colored teeth starting yellowish, brownish, to blackish and having a rough surface. The purpose of this case report is to obtain an overview of the care of Dental and Oral Health Services for Mr.Clients. S (22 years) with a case of tartar accompained by supernumerary teeth the design of writing by conducting assessment,estabilishing a diagnosis, arranging a treatment plan, implementing the implementation,compiling the results of the evaluation on the client Mr.S (22 years) with a case of tartar accompanied by supernumerary teeth in quadrant 2 there are two supernumerary teeth,in quadrant 3 there are two supernumerary teeth and in quadrant 4 there is one supernumerary teeth and subsequently documented. The method of caring for dental and oral health services is carried out by revealing data and facts in the medical record, observation, and interviews with clients. Furthermore and scaling treatments are performed. Conclusions from the results of the evaluation of care for dental and oral health services for Mr. S is the increase in knowledge and maintenance of dental and oral health of Mr. S after being given health promotion on how to maintain good and right dental and oral health. Key words: Care For Oral And Dental Health, Tartar, Supernumerary Teeth.